The Covid-19 Vaccine Production Club : Will Value Chains Temper Nationalism? - Evenett, Simon J.; Hoekman, Bernard; Rocha, Nadia; Ruta, Michele (World Bank, Washington, DC, 2021)
In the first two months of 2021, the production of COVID-19 vaccines has suffered setbacks delaying the implementation of national inoculation strategies. These delays have revealed the concentration of vaccine manufacture in a small club of producer nations, which in turn has implications for the degree to which cross-border value chains can deter more aggressive forms of Vaccine Nationalism, such as export curbs. This paper documents the existence of this club, taking account of not just the production of final vaccines but also the ingredients of and items needed to manufacture and distribute COVID-19 vaccines. During 2017–19, vaccine producing nations sourced 88 percent of their key vaccine ingredients from other vaccine producing trading partners. Combined with the growing number of mutations of COVID-19 and the realization that this coronavirus is likely to become a permanent endemic global health threat, this finding calls for a rethink of the policy calculus towards ramping up the production and distribution of COVID-19 vaccines, its ingredients, and the various items needed to deliver them. The more approved vaccines that are safely produced, the smaller will be the temptation to succumb to zero-sum Vaccine Nationalism.